Realities and perspectives of adolescent mothers in their first pregnancy - Rita de Cássia Andrade Neiva Santos; Raimunda Magalhães da Silva; Maria Veraci Oliveira Queiroz; Herla Maria Furtado Jorge; Aline Veras Morais Brilhante
ABSTRACT Objective: to understand the trajectory of adolescents regarding the first pregnancy, contemplating realities and perspectives. Method: qualitative study, based on the Schütz theoretical framework, with 30 adolescents assisted in an outpatient clinic for adolescents in Fortaleza, Ceará, Brazil. From the narrative interviews carried out in the first semester of 2013, in the return for the first consultation of the puerperium, the communicative processes were identified, the central ideas and units of meanings expressed in the themes were abstracted: I was dating and became pregnant; realities and perspectives. Results: adolescents justified pregnancy through sexual drive and insufficient prevention; they narrated the fear faced, difficulties in motherhood and continuity of studies. The realities coexisted with the prospects of family members and partners helping to educate the child to achieve a different future from what they themselves experienced. Final considerations: adolescents experienced motherhood with ambivalent conflicts because they were young mothers, but they wanted to raise and educate their children, even those with minimal living conditions.